Análise comparativa de duas modelagens teóricas 2D voltadas à interpretação de bacias sedimentares - ALEIXO, Mike Sullivan Silva da Paixão (2022)
We analyze the performance of two 2D gravimetric interpretations for delineating the basement relief surface of a sedimentary basins. The first method employs as interpretation model a set of prisms and the second one a discrete mobile operator compounded by ribbons. The operator is composed by horizontal 2D ribbons distributed along the horizontal and vertical directions. In the gravity interpretations, we use a 2D gravimetric inversion method that delineates discontinuous surfaces of the tops of the basement of the sedimentary basin displaying constant density contrast relative to surrounding crystalline rocks. This inversion method produces stabilized estimates of the depths of the top of the basement through the Total Variation (VT) functional. We apply both methods to synthetic and real data collected in Steptoe Valley, Nevada, United States.